A nonlocal coupled damage-plasticity model for concrete - Nguyen, G; Korsunsky, A (2007)
The paper presents a non-local constitutive model for the mechanical behaviour of concrete that is based on damage mechanics and plasticity theory. To model the material deterioration due to cracking and residual deformation due to friction, the presented model uses two loading surfaces corresponding to damage and plastic frictional mechanisms. Non-local regularization is used in this study, realized through the non-locality of the energy term in the damage loading function. The particular focus of this study is the calibration of the model parameters. It is shown that both the local behaviour parameters and the parameters governing the non-local material point interaction can be determined from experimental data reliably and consistently. A novel procedure is developed for parameter identification, using the separation of total dissipation energy into additive parts corresponding to different dissipation mechanisms. The relationship between the local and non-local parameters is also addressed, helping to obtain model responses consistent with the fracture energy of the material. © 2007 Taylor and Francis Group.